Multipurpose prevention technologies: Determination of an interest in its use for STI and contraception by Nigerian women - Joda, Arinola E.; Akapo, Abiodun; Ilomuanya, Chinonyelum S.; Ogundemuren, Deborah A.; Ofonabasi-Bassey, Peace; Ilomuanya, Margaret (The Nigerian Journal of Pharmacy, 2024)
Introduction: Multipurpose preventive technologies (MPTs) have the potential to address sexual and reproductive health requirements by concurrently protecting against HIV and unplanned pregnancy in a single product. The recognized lack of provision and knowledge of MPTs and contraceptives in general among Nigerian women between the ages 15-49 plays a large role in the occurrence of unintended pregnancies, its concurrent mismanagement, and the contraction and inefficient handling of HIVand other STI’s. Method: An online cross-sectional survey was conducted using Google Forms® distributed to the prospective respondents via WhatsApp platform across all geopolitical zones in Nigeria. Sexually active women (n = 393) currently residing in Nigeria were enrolled into the study following informed consent. Interest in MPT’s was evaluated using descriptive analysis with the sociodemographic characteristics of the participants as a factor. Results: Only 36% of the women had heard of MPTs prior to the study however, 86% of them expressed interest in the use of technologies that will protect them from unintended pregnancies and STIs including HIV. Income category and prior knowledge of MPTs were the only factors significantly linked to interest in MPTs. Other sociodemographic factors did not have much bearing on the interest in MPTs. Conclusion: Given the diversity of women’s tastes and their evolving needs in terms of sexual and reproductive health throughout their lives, choice is crucial when it comes to the provision of HIV and pregnancy prevention products. This study shows that the majority of the sexually active women in Nigeria are interested in MPTs. Women who have had their desired number of children and sexually active unmarried women who are at risk of contraction of STIs are interested in MPTs. Affordable pricing is crucial in sparking interest in its use so the pricing should be within an affordable range, as the data shows that the majority of the women are middle-income earners.